Real-world performance of the CALGB 10403 regimen in young adults in the United States - Brandon DaSilva; Alicia Darwin; Amy Zhang; Rutu D. Vyas; Kathryn Russell; Jason S. Gilbert; Virginia Tan; Susan Feldt; Hannah Johnston; Emily C. Liang; Adam S. DuVall; Michaela Liedtke; et al. (Blood Neoplasia)
Abstract: The Cancer and Leukemia Group B 10403 (C10403) trial prospectively demonstrated the safety and efficacy of administering an asparaginase-containing pediatric regimen for the treatment of adolescents and young adults (AYAs) with acute lymphoblastic leukemia. Since its implementation as standard of care, it is unknown how the C10403 regimen performs beyond the clinical trial setting. To bridge this knowledge gap, we designed a multicenter retrospective cohort study to examine the safety, efficacy, and challenges of completing C10403 in the “real world.” From October 2012 through June 2020, a total of 139 patients began induction as per the C10403 regimen across 6 US academic cancer centers. The median age was 26 years (range, 17-39), 69% were male, 55% were non-Hispanic White, and 27% were Hispanic. Among them, 122 patients (88%) achieved complete remission or complete remission with incomplete count recovery (CR/CRi) with C10403, 48 (35%) completed maintenance therapy, and 47 (34%) changed postremission regimens while in CR/CRi. The 3-year event-free survival (EFS) was 66% (95% confidence interval [CI], 55-74), and the 3-year overall survival (OS) was 81% (95% CI, 74-87). Four deaths occurred while on C10403 treatment: 1 during induction; and 3 later in the treatment course. The most common grade 3 or 4 adverse events during induction included alanine aminotransferase elevation (22%) and sepsis (14%). B-cell immunophenotype (hazard ratio [HR], 2.45; 95% CI, 1.09-5.48), Philadelphia chromosome–like genetics (HR, 3.05; 95% CI, 1.25-7.44), and Hispanic ethnicity (HR, 2.00; 95% CI, 1.06-3.78) were associated with worse EFS in univariate analyses. Overall, these real-world results are comparable to those of the C10403 trial. Further improvements are needed to enhance outcomes and regimen tolerability in the AYA population.